Gastric lavage may not be representative of total microplastic ingestion for a wild passerine bird - R. Keith Andringa; Nicholas A. Bruni; Jennifer A. Smith; Heather L. Prestridge; Ryan Thornton; Jacquelyn K. Grace (PLoS ONE, 2025)
Microplastic pollution has become a global concern and understanding its impact on wildlife requires effective sampling techniques that quantify exposure. In particular, non-lethal sampling techniques are needed for passerines for which microplastic exposure is poorly understood. In this study, we evaluated whether non-lethal proventricular gastric lavage can provide a representative sample of total microplastic ingestion in passerine birds. We sampled Brown-headed Cowbirds ( Molothrus ater ) (n = 105) from Government Canyon State Natural Area in San Antonio, Texas, United States (US). We performed gastric lavage to recover microplastics from each bird, before euthanizing them and dissecting gastrointestinal tracts. We recovered microplastics from 99% of birds. Gastric lavage recovered an average of 50.4% of ingested microplastics although recovery rate was highly variable (range: 0–100%, coefficient of variation: 59.52%), indicating much uncertainty in estimating individual total microplastic loads from gastric lavage. Sampling date influenced microplastic loads and recovery rates, which may be due to untested microplastic-environment interactions or may be an artifact of sampling conditions. Recovery rate was unaffected by time of day, bird age, sex, or body condition, or microplastic shape. Overall, our findings suggest that gastric lavage provides highly variable estimates of total gastrointestinal microplastics, and may be more appropriate for studies of recently ingested microplastics, only, that should be contained within the proventriculus.